La idiosincrasia de los servicios sociales en el medio rural salmantino - Morales Romo, Noelia (Cuadernos de Trabajo Social, 2007)
This paper is the outcome of research on Social Services in rural areas of Salamanca. The object of the study is seen from three points of view: that of the service professionals, that of other professionals who work in those rural areas, and finally that of the rural inhabitants themselves. Taking the characteristics of this area into account, this paper seeks to identify the difficulties and advantages that Social Service professionals face in an environment where the equality of opportunities is still a panacea.